الكفاية الوالدية وعلاقتها بمستوى المهارات الاجتماعية - رزاق لبزة, سميرة; عتيق, منى (جامعة الوادي - University of Eloued, 2021)
سعت الدراسة الحالية للكشف عن طبيعة العلاقة بين الكفاية الوالدية ومستوى المهارات الاجتماعية لدى الأطفال المصابين بالتوحد من وجهة نظر أوليائهم، واتبع في هذه الدراسة المنهج الوصفي التحليلي، تم تطبيق الدراسة على عينة عشوائية تألفت من (30) وليا يتابعون أطفالهم المصابين بالتوحد بمراكز وجمعيات التكفل بالتوحد بالوادي، وتم الحصول على البيانات باستخدام مقياس المهارات الاجتماعية، ومقياس الكفاية الوالدية، حيث تم اعدادهما للدراسة الحالية، توصلت الدراسة إلى ما يلي: • توجد علاقة ارتباطية دالة احصائيا عند مستوى الدلالة بين الكفاية الوالدية والمهارات الاجتماعية لدى الأطفال المصابين بالتوحد، • توجد فروق دالة احصائيا عند مستوى الدلالة في المهارات الاجتماعية لدى أطفالهم المصابين بالتوحد تعزى لمستويات الكفاية الوالدية من وجهة نظر أوليائهم • توجد فروق دالة احصائيا عند مستوى الدلالة ) في المهارات الاجتماعية لدى الأطفال المصابين بالتوحد تعزى لمستويي الكفاية الوالدي (المرتفعة / المنخفضة( من وجهة نظر أوليائهم. • لا توجد فروق في المهارات الاجتماعية لدى الأطفال المصابين بالتوحد تعزى لمتغير الجنس (ذكور/ إناث). Abstract: The current study sought to reveal the nature of the relationship between parental competence and the level of social skills of their autistic children from the point of view of their parents , The descriptive and analytical approach was followed in The current study. The study was applied to a random sample consisting of 30 parents who follow their autistic children in Eloued Centers and Associations for Autism. Data were obtained using the social skills scale and the parental competency scale, which were prepared for the current study. The study found the following: • the existence of a statistically significant correlation relationship at level significance (α =0.01(between parental competence and social skills in autistic children from the point of view of their parents. • the existence of a statistically significant differences at the level of significance (α =0.01( in social skills in autistic children due to the levels of parental competence from the point of view of their parents . • the existence of a statistically significant differences at the level of significance (α =0.01( in social skills in autistic children of their autistic children due to both (high/low) levels of parental competence from the point of view of their parents . • no significant differences in social skills in autistic children due to gender variable (male/female).
لدى الأطفال المصابين بالتوحد من وجهة نظر أوليائهم
مقال
Keywords: كفاية والدية؛ مهارات اجتماعية؛ أولياء الأطفال مصابين بالتوحد؛ اضطراب طيف التوحد؛ مستوى; Parental competence; social skills; autistic children; autism spectrum disorder